Methane formation driven by light and heat prior to the origin of life and beyond - Ernst, Leonard; Barayeu, Uladzimir; Hädeler, Jonas; Dick, Tobias P.; Klatt, Judith M.; Keppler, Frank; Rebelein, Johannes G. (Nature Communications, 2023)
Methane is a potent greenhouse gas, which likely enabled the evolution of life by keeping the early Earth warm. Here, we demonstrate routes towards abiotic methane and ethane formation under early-earth conditions from methylated sulfur and nitrogen compounds with prebiotic origin. These compounds are demethylated in Fenton reactions governed by ferrous iron and reactive oxygen species (ROS) produced by light and heat in aqueous environments. After the emergence of life, this phenomenon would have greatly intensified in the anoxic Archean by providing methylated sulfur and nitrogen substrates. This ROS-driven Fenton chemistry can occur delocalized from serpentinization across Earth’s humid realm and thereby substantially differs from previously suggested methane formation routes that are spatially restricted. Here, we report that Fenton reactions driven by light and heat release methane and ethane and might have shaped the chemical evolution of the atmosphere prior to the origin of life and beyond.
Gesehen am 16.01.2024